DYNAMIC SYSTEM MODELLING AND LAND SUITABILITY TO DEFINE PRIORITY AREAS OF SOYBEAN PLANTATION IN PADDY FIELDS IN KARAWANG, WEST JAVA - Widiatmaka, Widiatmaka; Ambarwulan, Wiwin; Firmansyah, Irman; Munibah, Khursatul; Santoso, Paulus B.K.; Sudarsono, Sudarsono (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
One of the agricultural public commodities in Indonesia which still cannot fulfill its domestic consumption needs is soybean. The objectives of the research, which was conducted in Karawang Regency, West Java, Indonesia, were to: (i) identify the suitable area for soybean plantations in paddy fields, (ii) Â assess the development of soybeans in land use and socio-economic context, and (iii) plan the spatially soybean plantation. A soil survey and land evaluation for soybean was completed. IKONOS imagery was applied to delineate paddy fields while a dynamic system modelling was developed using Powersim 8.0 software. The results of the research showed that the suitability class for soybean plantation in the paddy fields of Karawang Regency ranges from unsuitable (N) to suitable (S2), with limiting factors being temperature, fertility, nutrients retention, slope, erosion, rooting media and toxicity. Very limited arable land Â has been used so far for soybeans plantations due to low economic returns. The model predicts that, should the development of soybean continues in its business as usual path, a deficit of soybean will occur in 2030. The model provides alternative scenarios to reduce the deficit. Prioritization was done spatially using the suitable land gradually, corresponding to the government budget availability.